Modos de dizer do jornalismo impresso brasileiro : para além dos códigos, o regime de verdade nos dispositivos interacionais da notícia - Andrade, Josefa Melo e Sousa Bentivi (2016)
Assuming that the truth is the ontological category that regulates journalism and ensures social legitimacy to build knowledge about reality, this thesis analyzes the enunciative processes that constitute the ways of telling of the Brazilian printed journalism, by activating interactional devices of news, observing the Folha de São Paulo newspaper's regimen of truth in the construction of the enunciation about Fernando Henrique Cardoso (FHC) and Luiz Inacio Lula da Silva (Lula) as characters in the presidential election campaigns in 1994 and 2002. Truth and legitimacy are questionable and unstable in journalism, especially in times of institutional and political crisis, like is experienced in Brazil in 2016, when the society demands that journalism be faithful to the facts, attributing to this institution the responsibility to produce the truth about the events which makes the topic always updated and suitable to the scientific research. This study was conducted from three branches: the communication/media/journalism; studies on politics, on the relationship between communication and politics in Brazil and language studies in interlocutive dimension of language/pragmatic intrinsec conception and conversional approach; the linguistics of enunciation; the linguistics semantics and the semantics of the event. Four electoral conjuncture variables are identified from the political Science and are decisive in the presidential elections in Brazil, post-military dictatorship: economics; government; politics and ideology; and media. 'Unraveling the communication', it was found that into the variable media/journalism/news, other variables are established, what makes the media variable a vector that integrates other variables, a condition that potentiates the strategic action of journalism. The analysis of the enunciative process of the news shows that FHC and Lula, in the expository scene of the news, compete for a place or some countersigned space by what establishment determines. In this logic, the media/the journalism gives special attention to the maintenance of liberal/neoliberal economic system and chooses to build enunciative scenes positively framing characters who are responsible for the system maintenance, a condition that reaffirms journalism as a political institution, an institution whose regimen of truth is guided by the defense of an 'ideal program’ to the country that has found its 'perfect' form in the design and implementation of the Real Plan by Fernando Henrique Cardoso, and in the conciliation of a symbolic economy that Luiz Inacio Lula da Silva had to join.